IMPLEMENTATION ASPECT OF LAW NUMBER 11 OF 2010 IN EFFORTS TO IMPROVE THE ECONOMIC WELFARE OF THE COMMUNITY IN RELATION TO THE CONSERVATION OF CULTURAL HERITAGE - Erwin Mansyur Ugu Saraka; Muhammad Yaasiin Raya; Syarifuddin (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2025)
Abstract The transition from Law Number 5 of 1992 on cultural heritage to Law Number 11 of 2010 occurred because the previous law was deemed no longer aligned with the developments, demands, and legal needs of society. Therefore, a replacement was necessary. Moreover, Law Number 11 of 2010 is more focused on the involvement of the community in the management of cultural heritage. This aspect forms the basis of this research, which aims to examine the implementation of the law in relation to the preservation of cultural heritage for the enhancement of the economy and the well-being of society, as outlined in the articles of the law. Literature studies, legal analysis, and case studies are the methods employed in this research. Data analysis is conducted qualitatively with an inductive approach, alongside explanatory analysis to draw conclusions. As a result, several explanations within the articles of Law Number 11 of 2010 prioritise the enhancement of the economy and the well-being of society, both in terms of the paradigm of cultural heritage preservation and its management as an integrated effort to protect, develop spatial planning (zones), and utilise cultural heritage effectively. Furthermore, efforts to improve the welfare of the community through the management and utilisation of cultural heritage must be proportionate to the efforts made for its preservation. Keywords: Cultural Heritage, Law, Preservation, Community Welfare